2014
DOI: 10.7314/apjcp.2014.15.14.5551
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effects of HER-2/neu on Prognosis in Colorectal Cancer: a Meta-analysis

Abstract: Background: The prognostic value of human epidermal growth factor receptor-2 (HER-2/neu) for survival of patients with colorectal cancer (CRC) is still ambiguous. We therefore performed a meta-analysis to evaluate its prognostic significance. Materials and Methods: We searched the MEDLINE and EMBASE databases for published literature investigating associations between HER-2/neu status and overall survival of patients with CRC. A meta-analysis was performed using a DerSimonian-Laird model and publication bias w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
1
1
0
Order By: Relevance
“…In line with several studies of CRC patients [ 26 ][ 27 ], we did not find a prognostic benefit for patients with a positive HER-2 status or any correlation between positive HER-2 status and clinico-pathological parameters. As demonstrated in our preliminary studies [ 23 ], high HER-2 expression was found mainly in primary tumors in rectal cancer patients ( n = 4; 18.2%).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with several studies of CRC patients [ 26 ][ 27 ], we did not find a prognostic benefit for patients with a positive HER-2 status or any correlation between positive HER-2 status and clinico-pathological parameters. As demonstrated in our preliminary studies [ 23 ], high HER-2 expression was found mainly in primary tumors in rectal cancer patients ( n = 4; 18.2%).…”
Section: Discussionsupporting
confidence: 89%
“…In several published meta-analyses it has been shown that HER-2 overexpression was correlated with decreased survival in CRC patients suggesting that HER-2 overexpression might not be a prognostic indicator [ 26 ][ 27 ]. In metastatic CRC, Aprile et al [ 28 ] reported a negative prognostic value of HER-2 expression in brain metastases.…”
Section: Introductionmentioning
confidence: 99%